Exploring mouse necropsy through augmented reality: developing a web application for enhanced learning and visualization - Hasan Tarik Atmaca (Springer, 2024)
Abstract Necropsy, the examination of animal carcasses to determine the cause of death, is an essential skill for many professionals. Traditional training methods, however, are costly and time-consuming. The article suggests that Web-based Augmented Reality (WebAR) can offer an immersive and cost-effective training experience for laboratory animal necropsy. It describes using photogrammetry techniques to create a virtual necropsy environment consisting of 10 necropsy steps. A questionnaire was used to evaluate the usability, educational value, and drawbacks of the designed application by students who tested it. The paper outlines best practices for developing WebAR simulations, including high-fidelity 3D models and interactive elements. Additionally, it presents methods for creating new WebAR applications using specific programs or scripts. This paper highlights the potential benefits of WebAR for laboratory animal necropsy training, emphasizing its accessibility, cost-effectiveness, and scalability.